Feasibility of mail-based biospecimen collection in an online preconception cohort study - Koenig, Martha R.; Wesselink, Amelia K.; Kuriyama, Andrea S.; Chaiyasarikul, Alina; Hatch, Elizabeth E.; Wise, Lauren A. (Frontiers in Reproductive Health, 2023)
Background Prospective cohort studies that enroll participants before conception are crucial for deepening scientific understanding of how the preconception environment influences reproductive outcomes. While web-based research methods provide efficient and effective strategies to collect questionnaire-based data, few of these studies incorporate biospecimen collection, which can enhance the validity of exposure assessment. There is limited literature on the feasibility and cost-effectiveness of collecting biospecimens in web-based preconception cohort studies. Methods We evaluated the feasibility and cost-effectiveness of in-clinic and mail-based biospecimen collection in Pregnancy Study Online (PRESTO), a North American web-based preconception cohort study. Both members of the couple were eligible to participate if their conception attempt time was ≤3 months at enrollment. We invited study participants from the Boston, MA and Detroit, MI metropolitan areas to attend a study visit and provide urine and blood (hereafter “in-clinic protocol”). We invited all other participants to complete mail-based collection of urine and blood spots (hereafter “mail-based protocol”). We compared overall consent and protocol completion rates, demographic characteristics of those who consented and completed either of the protocols, and costs between mail-based and in-clinic protocols for biospecimen collection. Finally, we described logistical challenges pertaining to reliance on mail-based delivery of time-sensitive biospecimens compared with in-clinic methods. Results During January 2022-July 2022, 69% of female participants (134/195) and 42% of male participants (31/74) consented to participate in the mail-based protocol. Consent rates for the in-clinic protocol were 39% for female participants (289/739 during March 2014-July 2022) and 25% for male participants (40/157 during March 2017-July 2022). Participants who consented to participate were generally of higher socioeconomic position than non-participants. Deviations from the protocol occurred more frequently within the mail-based protocol but were easily corrected. The cost per participant enrolled was similar across protocols (mail-based: 276.14 vs. in-clinic: 270.38). Conclusions Our results indicate that mail-based collection of biospecimens may create opportunities to recruit a larger and more geographically diverse participant population at a comparable cost-per-participant enrolled to in-clinic methods.